Mesothelin is Commonly Expressed in Pancreatic Adenocarcinoma but Unrelated to Cancer Aggressiveness. (21st October 2021) - Weidemann, Sören; Perez, Daniel; Izbicki, Jakob R.; Neipp, Michael; Mofid, Hamid; Daniels, Thies; Nahrstedt, Ulf; Jacobsen, Frank; Bernreuther, Christian; Simon, Ronald; Steurer, Stefan; Burandt, Eike; et al.
Abstract: Data on Mesothelin (MSLN) expression in human normal and cancerous tissues is controversial. We employed immunohistochemistry (IHC) on a tissue microarray (TMA) from 599 pancreatic cancers and 12 large tissue sections of pancreatitis. MSLN expression was highest in pancreatic adenocarcinomas (89%) and adenocarcinomas of the ampulla Vateri (79%), infrequent in pancreatitis and absent in 6 acinus cell carcinomas and normal pancreas. MSLN expression was unrelated to pathological tumor stage, grade, metastasis, and tumor-infiltrating CD8+ lymphocytes. In conclusion, pancreatic cancer may be ideally suited for putative anti- MSLN therapies, and MSLN may represent a suitable biomarker for pancreatic cancer diagnosis, especially on small biopsies.